Maximization of quadruple phase boundary for alkaline membrane fuel cell using non-stoichiometric α-MnO2 as cathode catalyst. (8th January 2019) - Shi, X.; Ahmad, S.; Pérez-Salcedo, K.; Escobar, B.; Zheng, H.; Kannan, A.M.
Abstract: Oxygen can only be reduced at the quadruple phase boundary (catalyst, carbon support, ionomer and oxygen) of the cathode catalyst layer with non-conducting electrocatalyst. To maximize the quadruple phase boundary sites is crucial to increase the peak power density of each membrane electrode assembly. The quadruple phase boundary is depending on the ratio of catalyst, carbon support and ionomer. The loading of catalyst layer is also crucial to the fuel cell performance. In this study, non-stoichiometric α-MnO2 manganese dioxide nanorod material has been synthesized and the ratios of carbon, ionomer and catalyst loadings were optimized in alkaline membrane fuel cell. In total, ten membrane electrode assemblies have been manufactured and tested. Taguchi design method has been applied in order to understand the effect of each parameter. The conclusion finds out the ionomer has more influence on the alkaline membrane fuel cell peak power performance than carbon and loading. Highlights: Oxygen vacancy imbedded α-MnO2 catalyst as the cathode for alkaline fuel cell. Optimize the carbon:catalyst:ionomer ratios for cathode catalyst layer. Taguchi design method was used to determine the effect factor of each parameter.